Pengaruh Halal Lifestyle, Citra Merek dan Kualitas Produk pada Keputusan Pembelian Produk Nyai Mercon di Tiktok Shop di Kota Bengkulu - Devi Permata Sari; Eka Sri Wahyuni; Yenti Sumarni (Universitas Muhammadiyah Surabaya, 2026)
The purpose of this study was to analyze the influence of halal lifestyle, brand image, and product quality on purchasing decisions for products at TikTok Shop at Nyai Mercon Store in Bengkulu City. This study used quantitative methods with primary data in the form of questionnaires for 100 respondents and analysis using SEM-PLS using the SmartPLS 4 application. The results showed that the halal lifestyle variable had a positive and significant effect on purchasing decisions (coefficient 0.448; p-value 0.001). The brand image variable had a significant effect on purchasing decisions (coefficient 0.318; p-value 0.015). The product quality variable had a positive and significant effect on purchasing decisions (coefficient 0.226; p-value 0.026). This study shows that halal lifestyle, brand image, and product quality play a significant role in increasing purchasing decisions on TikTok Shop.